Ability of Ipomoea aquatica Forssk. to remediate phenol in water and effects of phenol on the plant's growth - Lee, Siew Yi; Ahmad, Siti Aqlima; Mustapha, Siti Roslina; Abdullah, Janna Ong (Universiti Putra Malaysia Press, 2017)
Despite wide applications in industries, phenol pollution leads to many health effects, and one of the technologies used to clean up phenol pollution is phytoremediation. The aim of this research was to assess the remediation ability of Ipomoea aquatica Forssk., which is easy to handle and and has a fast growth rate. Plantlet was grown in water spiked with 0.05, 0.10, 0.20, 0.30 and 0.40 g/L phenol, followed by daily observation of the plantlets morphology and tracking of phenol concentration in the water and plantlet extracts via 4-aminoantipyrine (4-AAP) assay. Plantlet's roots in 0.10 g/L phenol (57.42 ± 1.41 mm) were significantly longer (p < 0.05) than those of the control plantlets (43.57 ± 3.87 mm) in contrast to other phenol concentrations which had stunted roots growth. I. aquatica Forssk. was able to survive with 0.30 g/L phenol despite exhibiting yellowing of leaves and increased sensitivity to scarring on the stems. The plantlets were able to completely remove the phenol from the water spiked with phenol at 0.05 g/L after 12 days of growth. However, the highest average rate of phenol removal was 0.021 g/L/day from water spiked with 0.30 g/L phenol. Phenol analysis on the plantlets' extracts revealed that I. aquatica Forssk. had degraded the absorbed phenol. This observation is of significant interest as it highlights the potential of I. aquatica Forssk. for use as a phytoremediator to clean up phenol contaminated water.